The classic tale of Peter Rabbit and other cherished stories - Potter, Beatrix, 1866-1943.; Santore, Charles (Philadelphia, Pa. : Courage Books, 1986)
Presents a selection of stories by the well-known author.
Keywords: Children's stories, English; Animals -- Fiction; Animals -- Fiction; Rabbits -- Fiction; Animals -- Fiction